2009
DOI: 10.1021/bc900309n
|View full text |Cite
|
Sign up to set email alerts
|

Tris-Nitrilotriacetic Acids of Subnanomolar Affinity Toward Hexahistidine Tagged Molecules

Abstract: Nitrilotriacetic acid (NTA) has moderate affinity (10 µM) for hexahistidine (His6) and is widely used in the purification of His6-tagged proteins. The affinity can be increased significantly (10 nM) through multivalency such as using a tris-NTA. We show that the binding affinity of tris-NTA is dependent on the flexibility and length of the spacer between the mono-NTA and the scaffold: the shorter the spacer, the higher the affinity. A series of biotinylated tris-NTA having different spacers were synthesized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 23 publications
4
72
0
Order By: Relevance
“…The present study demonstrates that reversible, highly effective MHC-peptide multimers can be prepared based on Ni 2ϩ -NTAHis tag chelate complexes. Previously branched tri-NTA complexes have been described that have up to subnanomolar K D for His 6 and His 10 tags (22)(23)(24). Our results demonstrate that highly stable chelate complexes can be formed with linear peptides carrying orthogonal NTA moieties; the binding of Ni 2ϩ -NTA 4 peptide (compound 4) to 2ϫHis 6 -tagged A2/Flu complexes with a K D of 19.6 pM is the highest affinity ever reported for NTA-His tag complexes ( Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The present study demonstrates that reversible, highly effective MHC-peptide multimers can be prepared based on Ni 2ϩ -NTAHis tag chelate complexes. Previously branched tri-NTA complexes have been described that have up to subnanomolar K D for His 6 and His 10 tags (22)(23)(24). Our results demonstrate that highly stable chelate complexes can be formed with linear peptides carrying orthogonal NTA moieties; the binding of Ni 2ϩ -NTA 4 peptide (compound 4) to 2ϫHis 6 -tagged A2/Flu complexes with a K D of 19.6 pM is the highest affinity ever reported for NTA-His tag complexes ( Fig.…”
Section: Discussionsupporting
confidence: 62%
“…In compound 2, this distance is shorter than in compound 3. A previous study has shown that the avidity of branched tri-Ni 2ϩ -NTA molecules for His 6 -tagged molecules increased with the decreasing length of the spacer linking the NTA moieties to a central nitrogen (24). This argues that the NTA dimer compound 2 exhibited more avid binding than dimer compound 3, because of the shorter spacing distance xЈ.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, antibody responses to NTA-anchored antigens may be improved through further modifications of the NTA moiety to increase the affinity and stability of the NTA-polyhistidine interaction. Potential modifications include further increasing NTA valency (27), modifying the flexibility and length of the spacer between the mono-NTA and the scaffold (21), and incorporating hydrophobic shielding groups that impede removal of the chelated metal. These approaches are discussed in greater detail in recent publications from our laboratory (21,37).…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we and others have developed facile synthetic routes to multivalent nitrilotriacetic acid adaptors with nanomolar affinities for polyhistidine-tagged proteins (K D [equilibrium dissociation constant], ϳ10 M and ϳ1 nM for monovalent and trivalent NTA [tris-NTA], respectively) ( Fig. 1) (3,21,22,27). This approach has shown promise for in vivo delivery; most notably, plasma membrane vesicles to which polyhistidinylated dendritic cell-targeting moieties and costimulatory molecules were engrafted via trivalent NTA elicited functional antitumor immunity upon administration to mice (44).…”
mentioning
confidence: 99%
“…2,3-Diaminoacids and their derivatives have attracted a great deal of attention due to their application as key structural fragments of biologically active compounds [1]- [7], and/or as ligands for metal complexes [8]- [13]. Various methods to prepare these compounds have been reported [1] [2] [4] [14]- [19].…”
Section: Introductionmentioning
confidence: 99%